Are corporate social responsibility disclosures relevant for lenders? Empirical evidence from France. Issue 2 (27th November 2019) - Hamrouni, Amal; Uyar, Ali; Boussaada, Rim
Abstract : Purpose: The purpose of this paper is to test whether or not CSR disclosure (i.e. aggregate as well as its three sub-indicators) reduces the cost of debt for French corporations listed in the SBF 120 index between 2010 and 2015. Design/methodology/approach: CSR disclosure ratings of firms were collected from the Bloomberg database under three dimensions such as environmental, social and governance (ESG). Then, a pooled regression analysis was run. Findings: The results indicate that overall CSR disclosure score as a combination of ESG disclosure scores has a negative effect on the cost of debt (i.e. lowers the cost of debt). While environmental disclosure is negatively associated with the cost of debt, social disclosure is unexpectedly positively associated, and governance disclosure has an insignificant association with the cost of debt. Research limitations/implications: The study has two main limitations. First, the analysis does not consider contractual constraints and obligations that might exist in debt contracts (Jung et al., 2018). Second, the analyses cover a specific time period (i.e. between 2010 and 2015) for a specific country (i.e. France) excluding utilities and the financial sector. Practical implications: Overall, it is inferred from the results that financial markets for lenders take into account CSR disclosure when assessing the creditworthiness of borrowers. Specifically, environmental disclosure is the only subdimension of CSR that is influential on creditors' decisions to offer favorable interest rates. In line with this outcome, companies can assess their processes and be more aligned with eco-friendly practices, and investors are particularly advised to invest in those types of firms. Originality/value: This study extends scant literature on the association between CSR and the cost of debt by exploring how creditors treat CSR dimensions dissimilarly in granting loans to firms. The findings of this study have particular importance as financial debt is one of the most predominant forms of external financing.